PENDAMPINGAN PENYUSUNAN RENCANA STRATEGIS, IMPLEMENTASI VISI MISI DAN EVALUASI KEGIATAN YANG EFEKTIF EFISIEN MENCAPAI SMK PUSAT KEUNGGULAN (SMK PK) - I Made Indra P; Fanny Novika (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
The Central Vocational School of Excellence (SMK PK) is one of the priority programs of the Directorate General of Vocational Education (Ditjen Vocational Education) of the Ministry of Education and Culture in 2021. This program is an effort to develop Vocational High Schools with certain expertise programs in order to improve quality and performance, as well as become a reference for other schools . The Center for Excellence Vocational School program carries the spirit of Independent Learning which focuses on strengthening human resources and bringing the world of education closer to the professional world. Formulation of strategic plans, implementation of vision and mission and evaluation of activities that are effective and efficient in achieving the Center of Excellence Vocational High School PK is one of the activities to achieve and meet the targets of a SMK became SMK PK. This community service activity is carried out in the form of vocational assistance by STMA Trisakti to Wahidin Cirebon Vocational School. This mentoring activity will be held on Thursday, August 19, 2021, until October 11, 2021, online and offline. Overall SMK Wahidin Cirebon has completed the preparation of the strategic plan, the implementation of the vision and mission and the evaluation of activities have been well structured and directed